SLEEP QUALITY AND INNOVATION BEHAVIOR:CREATIVE SELF-EFFICACY AS A MEDIATOR AND SELF-ORIENTED PERFECTIONISM AS A MODERATOR - Hsin-Yi Huang (PEOPLE: International Journal of Social Sciences, 2026)
In today’s competitive and fast-paced work environment, innovative behavior is essential for individual and organizational growth. Prior research has mainly focused on external stressors and organizational contexts, with less attention to how employees’ psychological resources and personal traits influence innovative behavior, particularly through sleep quality. Drawing on Conservation of Resources Theory and Self-Efficacy Theory, this study examines the relationship between sleep quality and innovative behavior, the mediating role of creative self-efficacy, and the moderating role of self-oriented perfectionism. This study employed a convenience-sampling questionnaire survey. A total of 122 responses were collected, and after excluding invalid samples, 109 valid responses were retained for analysis. Results showed that better sleep quality positively predicts innovative behavior, and creative self-efficacy fully mediates this relationship. However, self-oriented perfectionism did not significantly moderate the relationship between creative self-efficacy and innovative behavior. The findings suggest that organizations can foster innovative behavior by promoting healthy work routines, work–life balance, positive feedback, and a learning-oriented culture that supports employee rest and psychological safety.